Are U.S. GAAP-based and IFRS-based accounting amounts more comparable after the revised lease standards? Evidence from ASC 842 and IFRS 16 - Altamuro, Jennifer; Chen, Lucy Huajing; Li, Yiwen (Review of Accounting Studies, 2025)
Abstract This study examines whether the revised lease standards (ASC 842 and IFRS 16) make U.S. GAAP-based accounting amounts more comparable with IFRS-based accounting amounts. Our study is motivated by the FASB and the IASB’s call for research on the comparability of the revised lease standards. We find that U.S. GAAP and IFRS pairs that are high operating lease users experience a larger increase in accounting comparability after the adoption of revised lease standards than low operating lease U.S. GAAP-IFRS pairs. Additionally, our results suggest that the improvement comes more from the changes to the balance sheet rather than the income statement and is more pronounced for IFRS firms from countries with stronger accounting enforcement. Lastly, we show that analysts who are more GAAP-focused (IFRS-focused) prior to the standard change are more likely to increase their forecasting of book value per share for IFRS (U.S. GAAP) firms.